2015
DOI: 10.4206/agrosur.2015.v43n2-07
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de cenizas volcánicas del Cordón Caulle sobre parámetros de calidad física en suelos agrícolas del sur de Chile

Abstract: Chile is exposed to the constant activity of their volcanoes, which during the eruptions released ashes that had formed soils of south-central Chile (Andisols) during the holocene. The last June of 2011, Cordon Caulle volcano recorded eruptive activity, releasing a great quantity of volcanic materials that were deposited on soils under different land uses, generating environmental problems and uncertainties among farmers for its handling. The aim of this study was to evaluate the effect of the incorporation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Several studies have assessed the impact of tephra deposition from different perspectives: tree-growth (Magnin et al, 2017), soil properties (Cremona et al, 2011; González et al, 2015), fauna changes (Berenstecher et al, 2017; Lallement et al, 2014) and leaf-litter decomposition (Chaneton et al, 2014; Piazza et al, 2018), among others. However, all these investigations have evaluated the impact of ash deposition at a short time scale, and potential long-term effects or the lack therefore are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the impact of tephra deposition from different perspectives: tree-growth (Magnin et al, 2017), soil properties (Cremona et al, 2011; González et al, 2015), fauna changes (Berenstecher et al, 2017; Lallement et al, 2014) and leaf-litter decomposition (Chaneton et al, 2014; Piazza et al, 2018), among others. However, all these investigations have evaluated the impact of ash deposition at a short time scale, and potential long-term effects or the lack therefore are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of volcanic soils with high mineral content is determined by the influence of climatic conditions and the effect of time for particle degradation and distribution through various physical and chemical alteration processes such as dissolution, leaching, and the precipitation of compounds, while the minerals that make up the ashes change shape, size, and porosity [7]. González et al, 2022 [8] found that the addition of ash in soil with a clay loam texture improved the water retention capacity and aeration, causing a dilution effect on some components (such as organic matter, phosphorus, calcium, and magnesium), as well as a decrease in pH and the electrical conductivity of the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Se registraron cambios en el crecimiento radial de los árboles, la productividad foliar y los niveles de herbivoría del dosel (Chaneton et al 2014;Magnin et al 2016). Las cenizas alteraron las propiedades físico-químicas del suelo, que incluyeron una mayor capacidad de retención hídrica y un menor contenido de nutrientes (Cremona et al 2011;González et al 2015;Berenstecher et al 2016). Los efectos en los organismos del suelo implicaron tanto reducciones en la abundancia de artrópodos y detritívoros (Elizalde 2014;Oleiro 2015), como la estimulación de la actividad de descomponedores (Berenstecher et al 2016).…”
unclassified